2016
DOI: 10.1016/j.wasman.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

An environmental benign process for cobalt and lithium recovery from spent lithium-ion batteries by mechanochemical approach

Abstract: a b s t r a c tIn the current study, an environmental benign process namely mechanochemical approach was developed for cobalt and lithium recovery from spent lithium-ion batteries (LIBs). The main merit of the process was that neither corrosive acid nor strong oxidant was applied. In the proposed process, lithium cobalt oxide (obtained from spent LIBs) was firstly co-grinded with various additives in a hermetic ball milling system, then Co and Li could be easily recovered by a water leaching procedure. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(70 citation statements)
references
References 49 publications
1
68
0
1
Order By: Relevance
“…In addition, the results revealed that the peak intensity of the activated samples decreased, and the full width at half maximum (FWHM) of all peaks was also broadened dramatically with the increase of the ball-milling time (Fig. 3), indicating that the crystal structure of the particles was destroyed and gradually transformed to an amorphous state due to the friction and impact during grinding 35,38 process. Furthermore, both the changes of the crystallite size and the degree of disorder also reflected that the LiCoO crystal was 2 subjected to crushing and became amorphous.…”
Section: Evaluation Of Mechanical Activation Processmentioning
confidence: 99%
“…In addition, the results revealed that the peak intensity of the activated samples decreased, and the full width at half maximum (FWHM) of all peaks was also broadened dramatically with the increase of the ball-milling time (Fig. 3), indicating that the crystal structure of the particles was destroyed and gradually transformed to an amorphous state due to the friction and impact during grinding 35,38 process. Furthermore, both the changes of the crystallite size and the degree of disorder also reflected that the LiCoO crystal was 2 subjected to crushing and became amorphous.…”
Section: Evaluation Of Mechanical Activation Processmentioning
confidence: 99%
“…The process flowchart is shown in Figure 15. Apart from processes discussed herein, other ones are summarized in Table S9 and Table S10 in supplementary Information [196][197][198][199][200][201][202][203][204][205].…”
Section: Organic Acid Leachingmentioning
confidence: 99%
“…Osnovni princip hemijskog taloženja je prevođenje jona metala iz rastvora dobijenog u procesu luženja u nerastvoran oblik i to najčešće posred-stvom NaOH [64,104]. Pomenuti proces je najzastupljeniji prilikom uklanjanja i valorizacije Al, Fe i Cu, ali je u više radova [98,117,[133][134] hemijska precipitacija korišćena i za selektivno taloženje jona metala iz rastvora pomoću različitih reagenasa.…”
Section: Solventna Ekstrakcijaunclassified